"أثر التفكير الاستراتيجي على جودة الحياة الوظيفية ""دراسة لآراء عينة من موظفي مجموعة مؤسسات روائح الورود بالوادي - الحاجة مباركة, خياري (University of eloued جامعة الوادي, 2021)
" التفكير الاستراتيجي هو القدرة على افتراض سيناريوهات محتملة الحدوث في المستقبل ،انطلاقاً من الوضع الراهن للمؤسسة من أجل تحقيق أهدافها و غاياتها ،و هذا يكون مرهوناً بمدى وعي أصحاب القرار فيها ،بضرورة خلق بيئة عمل معنوية وصحية مناسبة للموظفين ،لضمان الأمان الوظيفي و الفعالية الإنتاجية و للاستثمار الأمثل للقدرات الإبداعية الكامنة فيها.و من هذا المنطلق تكمن إشكالية الدراسة التي تحاول معالجة أثر التفكير الاستراتيجي على جودة الحياة الوظيفية . حيث تم الاستعانة بالاستبيان كأداة بحثية للوصول إلى النتائج المراد تحقيقها من هذه الدراسة،و تم الاستعانة ببرنامج SPSS)) لمعالجة هذه النتائج .و قد توصلت هذه الدراسة إلى أنه: - يوجد أثر ذو دلالة إحصائية للنوايا الإستراتيجية و للتصور النظمي في جودة الحياة الوظيفية بمؤسسات الورود بالوادي عند مستوى دلالة (0.05). -بينما لا يوجد أثر ذو دلالة إحصائية لقيادة الافتراضات وللتفكير الشمولي في جودة الحياة الوظيفية بمؤسسات الورود بالوادي عند مستوى دلالة (0.05). - وأسفرت نتائج اختبار Anova أنه لا يوجد فروق في جودة الحياة الوظيفية من حيث متغير (الجنس،العمر،الخبرة المهنية)، ولكن يوجد فروق ذو دلالة إحصائية من حيث متغير (المستوى التعليمي). ""Strategic thinking is the ability to hypothesize possible scenarios in the future, based on the current situation of the institution in order to achieve its goals and objectives, and this is contingent on the awareness of decision-makers in it, of the need to create an appropriate moral and healthy work environment for employees, to ensure job security and production effectiveness. For the optimal investment of the creative capabilities inherent in it. And from this point of view lies the problem of the study, which attempts to address the impact of strategic thinking on the quality of career life. Where the questionnaire was used as a research tool to reach the results to be achieved from this study, and the SPSS program was used to address these results. And this study concluded that: Roses in the valley at the level of significance (0.05). While there is no statistically significant effect of leading assumptions and holistic thinking on the quality of career life in Al-Ward institutions in the valley at the level of significance (0.05). - The results of the Anova test revealed that there are no differences in the quality of work life in terms of the variable (gender, age, professional experience), but there are statistically significant differences in terms of the variable (educational level). "
ماستر اقتصاد
Keywords: التفكير الاستراتيجي، جودة الحياة الوظيفية،التفكير الشمولي،التصّور النّظمي.النوايا الإستراتيجية ،قيادة الافتراضات.; strategic thinking, quality of work life, holistic thinking, systems visualization, strategic intentions, leadership assumptions.